A large-capacity bacteria-resistant adsorption resin for water treatment and preparation method thereof
Through the combination of a variety of monomer copolymerization, chloromethylation, quaternary amination and porous calcium carbonate framework, the problems of insufficient capacity and unstable skeleton of adsorption resin were solved, and an adsorption resin with large capacity and high mechanical strength was prepared, which was suitable for water treatment.
Patent Information
- Application Number
- CN202411956281.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-08
AI Technical Summary
The capacity of the existing adsorbent resin is insufficient, which cannot meet the large-displacement wastewater treatment. At the same time, its internal skeleton is unstable and its mechanical strength is insufficient.
By copolymerizing monomers such as styrene, divinylbenzene, methyl acrylate, etc., chloromethylation and quaternary amination, porous calcium carbonate is added as a skeleton during the preparation process, combined with long-chain alkyl grafting, an adsorption resin with large capacity and high mechanical strength is prepared.
The prepared adsorption resin has a large adsorption capacity and high cleanliness. It is not easy to be blocked by mold after long-term use, maintaining a large adsorption capacity and is suitable for water treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to an adsorption resin, and more particularly, to a large-capacity adsorption resin for water treatment and a preparation method thereof. Background Art
[0002] In order to meet the requirements of environmental protection and sustainable development, people have tried to develop adsorbent materials that have good adsorption effects and do not pollute the environment in recent years to increase the reuse rate of water and reduce emissions. Adsorption resin is a resin adsorption material with a porous three-dimensional structure. It has the characteristics of porosity, high cross-linking degree, and large specific surface area. It is widely used in wastewater treatment, drug separation and purification, etc. It has a high purification level and can be used repeatedly. However, the capacity of the current adsorption resin is insufficient and cannot meet the large-volume wastewater treatment. The internal skeleton of the resin with large capacity is unstable and the mechanical strength is insufficient. Therefore, how to provide an adsorption resin with a large capacity so that it can maintain the water treatment effect for a long time is a problem that needs to be solved at present. Summary of the invention
[0003] In order to solve the problems of low adsorption capacity and low cleanliness of adsorption resin, the present application provides a large-capacity adsorption resin for water treatment and a preparation method thereof.
[0004] In a first aspect, the present application provides a method for preparing a large-capacity adsorption resin for water treatment, comprising the following steps: S1: Evenly mix styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene to obtain a monomer formulation; evenly mix water, cellulose, calcium carbonate, boric acid, calcium chloride, and sodium chloride to obtain an aqueous phase mixture; evenly mix the monomer formulation and the aqueous phase mixture, raise the temperature, and keep the temperature to react to obtain a polymer; S2: washing the polymer with water, washing with an organic solvent, drying the powder and sieving it to obtain an intermediate product; S3: uniformly mix the intermediate product, monochloromethyl ether, sulfuric acid and catalyst, raise the temperature, keep the temperature for reaction, lower the temperature, wash with organic solvent, distill, add liquid alkali, adjust the pH, stir, filter, and obtain chloromethylated beads; S4: adding trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridylamine, methylal, and urotropine dropwise to the chloromethylated beads, raising the temperature, keeping the temperature to react, filtering, and distilling to obtain quaternized beads; S5: The quaternized beads are washed with water, converted with hydrochloric acid, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0005] By adopting the above scheme, the preparation method is relatively simple, the polymerization is relatively complete, the intermediate product obtained is copolymerized by styrene, divinylbenzene and methyl acrylate, the polymerization process is evenly dispersed, the average pore size of the obtained adsorption resin is large, the specific surface area is large, and the adsorption capacity is large. The intermediate product is first chloromethylated and then quaternized, and the quaternized adsorption resin obtained has better hydrophilicity and a certain bactericidal effect. The adsorption resin is not easily blocked by mold after long-term use and maintains a large adsorption capacity for a long time.
[0006] By adding monochloromethyl ether as a chlorinating agent, the reaction activity is high, the chlorination is sufficient, and the intermediate product can be well swollen. By adding a certain mass of sulfuric acid, the forward reaction is further promoted. After swelling, the interior of the intermediate product is also fully chloromethylated. The obtained chloromethylated beads have a uniform structure and high reaction activity.
[0007] Preferably, the catalyst is one or more of zinc oxide and iron oxide.
[0008] Preferably, the catalyst is zinc oxide. Using zinc oxide as a catalyst, the chloromethylation reaction is milder, the obtained chloromethylation beads react more fully, have a uniform structure and a large capacity.
[0009] In a specific embodiment, the weight parts of the components in the monomer formulation in S1 are as follows: 200-250 parts of styrene, 180-250 parts of divinylbenzene, 15-40 parts of methyl acrylate, 40-60 parts of toluene, 50-100 parts of isobutanol, 50-100 parts of normal alkanes, 100-200 parts of liquid wax, 100-200 parts of gasoline, 2-5 parts of BPO, 3-5 parts of AIBN, 5-10 parts of liquid bromine, and 5-10 parts of nitrobenzene; the weight parts of the components in the aqueous phase mixture are as follows: 2000-2200 parts of water, 5-10 parts of cellulose, 5-10 parts of calcium lignin sulfonate, 5-10 parts of boric acid, 50-70 parts of calcium chloride, 50-80 parts of sodium chloride, 2-10 parts of methylene blue, and 5-10 parts of gelatin; The mass volume ratio of the components in S3, the catalyst is zinc oxide, the intermediate product, monochloromethyl ether, sulfuric acid, and zinc chloride is: 4:10:1:1; The mass volume ratio of chloromethylated beads, trimethylamine, dimethylamine, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine in S4 is 2:(1.8-2.1):(1.8-1.9):(1-1.1):(2-2.2):1:(3-3.5):2.
[0010] By adopting the above scheme, the preparation steps suitable for the present application are high in yield, less impurities, less side reactions, appropriate degree of cross-linking, and the obtained adsorption resin has a uniform structure and a large capacity.
[0011] In a specific implementation scheme, the heating and heat preservation reaction in S1 includes the following steps: first heating to 78-82°C, keeping warm for 2-3 hours, then heating to 85-89°C, keeping warm for 5.5-6.5 hours, and finally heating to 93-97°C, keeping warm for 2.5-3.5 hours, and cooling to below 70°C.
[0012] By adopting the above scheme, the polymerization speed is uniform, not easy to explode, and the resin obtained by polymerization has a uniform structure, a small number of branches, a small number of by-products, a large specific surface area and a high porosity.
[0013] In a specific implementation scheme, the water washing and organic solvent washing in S2 include the following steps: washing with 50-80°C water until the water is clear, then introducing 60-80°C toluene to elute until the liquid wax and styrene residues are less than 100 ppm, then introducing 50-60°C methanol to elute until the toluene residue is less than 100 ppm, and finally washing with water until no solvent remains.
[0014] By adopting the above scheme, the residual solvent on the resin is fully washed, and the obtained adsorption resin has a high degree of cleanliness and is suitable for water treatment.
[0015] In a specific implementation scheme, the heating temperature in S3 is 48-50°C, the insulation reaction time is 9.5-10.5 hours, the cooling temperature is less than 30°C, the organic solvent washing includes methanol or methylal washing 2-4 times, the pH value is 8-10, and the stirring time is greater than 0.5 hour.
[0016] By adopting the above scheme, the reaction temperature is appropriate, the degree of swelling of the intermediate product is appropriate, the internal chloromethylation is sufficient without destroying the resin skeleton, and the obtained adsorption resin has a large capacity.
[0017] In a specific embodiment, the temperature of S4 is raised to 28-32°C, and the insulation reaction time is 9-11 hours.
[0018] By adopting the above scheme, the beads are fully quaternized, and the obtained adsorption resin has good hydrophilicity and large adsorption capacity, and is suitable for water treatment.
[0019] In a specific embodiment, the monomer formulation in S1 further includes 20-30 parts by mass of porous calcium carbonate.
[0020] Porous calcium carbonate has high strength, large specific surface area and good chemical stability. By adding a certain mass of porous calcium carbonate into the monomer formulation, the obtained polymer is polymerized along the porous calcium carbonate as a skeleton. The obtained adsorption resin has higher strength and larger surface area, and can maintain the wastewater treatment effect at a lower cross-linking density.
[0021] In a specific embodiment, the method further comprises the following steps: adding the quaternized beads and the long-chain halogenated alkane prepared in S4 to isopropanol, stirring evenly, and heating for reaction.
[0022] By adopting the above scheme, long-chain halogenated alkanes are introduced into the surface of the quaternized beads. The long-chain halogenated alkanes form a certain entanglement, making the porous calcium carbonate more stable and firm in the adsorption resin, so that the adsorption resin obtained maintains a large adsorption capacity for a long time.
[0023] In a specific embodiment, the long-chain halogenated alkane includes 1-bromododecane and 1-bromooctadecane in a mass ratio of 1:(1.2-1.4).
[0024] By adopting the above scheme, long and short chains are interlaced, and the structure of the obtained adsorption resin is more stable and less likely to fail.
[0025] In a second aspect, the present application provides a large-capacity adsorption resin for water treatment, which is prepared using the above steps.
[0026] The adsorption resin prepared by the above steps is fully chloromethylated and quaternized, has an appropriate degree of cross-linking, a stable mechanical skeleton, a large adsorption capacity, high cleanliness, and is suitable for water treatment.
[0027] In summary, this application has the following beneficial effects: 1. The present application prepares an adsorption resin by co-polymerizing a plurality of monomers and then chloromethylating and quaternizing them, and limits the process parameters of each step. The obtained adsorption resin has an appropriate degree of cross-linking, a stable mechanical skeleton during the swelling process, and is fully quaternized. The obtained adsorption resin has a large capacity and high cleanliness and is suitable for water treatment.
[0028] 2. The present application improves the strength and specific surface area of the adsorption resin by adding a certain mass of porous calcium carbonate to provide a skeleton effect during the preparation of the adsorption resin, making it have both large capacity and high strength, and more suitable for recycling and water treatment. By grafting long-chain alkyl groups on the surface of the quaternized beads and further limiting the long-chain alkyl groups to a certain mass ratio of 1-bromododecane and 1-bromooctadecane, a certain entanglement is formed between the long and short chains, making the adsorption resin structure with porous calcium carbonate as the skeleton more stable and having a longer service life. DETAILED DESCRIPTION
[0029] To further help understand the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All the embodiments described are only partial embodiments of the present invention, not all of them; the embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. The following embodiments are further explanations of the present invention, and the present invention is not limited thereto.
[0030] The other experimental reagents, unless otherwise specified, were conventional commercial brands or obtained through conventional preparation processes. Example
[0031] Example 1 This embodiment includes the following components by mass: 200g of styrene, 180g of divinylbenzene, 40g of methyl acrylate, 60g of toluene, 100g of isobutanol, 100g of normal alkanes, 200g of liquid wax, 200g of gasoline, 5g of BPO, 3g of AIBN, 10g of liquid bromine, 5g of nitrobenzene; 2000g of water, 5g of cellulose, 5g of calcium lignin sulfonate, 5g of boric acid, 50g of calcium chloride, 80g of sodium chloride, 10g of methylene blue, and 10g of gelatin.
[0032] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0033] Example 2 This embodiment includes the following components by mass: 250g styrene, 250g divinylbenzene, 15g methyl acrylate, 60g toluene, 50g isobutanol, 50g normal alkanes, 100g liquid wax, 100g gasoline, 5g BPO, 3g AIBN, 10g liquid bromine, 5g nitrobenzene; 2200g water, 5g cellulose, 5g calcium lignin sulfonate, 5g boric acid, 50g calcium chloride, 50g sodium chloride, 2g methylene blue, and 5g gelatin.
[0034] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0035] Example 3 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, and 7g gelatin.
[0036] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0037] Example 4 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, and 7g gelatin.
[0038] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 89° C., kept warm for 8 hours, and finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0039] Example 5 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, and 7g gelatin.
[0040] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78°C, kept warm for 2 hours, then heated to 89°C, kept warm for 6.5 hours, finally heated to -97°C, kept warm for 3.5 hours, and cooled to 60°C to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 25°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0041] Example 6 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, and 7g gelatin.
[0042] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 7, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0043] Example 7 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, 7g gelatin, and 25g porous calcium carbonate.
[0044] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride, sodium chloride, and porous calcium carbonate are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, and finally heated to 97° C., kept warm for 3.5 hours, and then cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0045] Example 8 This embodiment includes the following components by mass: 220g of styrene, 220g of divinylbenzene, 30g of methyl acrylate, 50g of toluene, 80g of isobutanol, 80g of normal alkanes, 150g of liquid wax, 150g of gasoline, 3g of BPO, 3g of AIBN, 8g of liquid bromine, 8g of nitrobenzene; 2100g of water, 8g of cellulose, 8g of calcium lignin sulfonate, 8g of boric acid, 60g of calcium chloride, 70g of sodium chloride, 7g of methylene blue, 7g of gelatin, 25g of porous calcium carbonate, 100g of 1-bromododecane, 100g of 1-bromooctadecane, and 2000ml of isopropanol.
[0046] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride, sodium chloride, and porous calcium carbonate are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, and finally heated to 97° C., kept warm for 3.5 hours, and then cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: adding quaternized beads, 1-bromododecane and 1-bromooctadecane into isopropanol, mixing evenly, heating at 70° C. for reaction, and filtering after 6 hours to obtain grafted beads; S6: Wash the grafted beads with water, transform them with hydrochloric acid for 1 hour, filter, wash them with water, and dry them to obtain a large-capacity adsorption resin.
[0047] Example 9 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, 7g gelatin, 25g porous calcium carbonate, 87g 1-bromododecane, 113g 1-bromooctadecane, and 2000ml isopropanol.
[0048] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride, sodium chloride, and porous calcium carbonate are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, and finally heated to 97° C., kept warm for 3.5 hours, and then cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: adding quaternized beads, 1-bromododecane and 1-bromooctadecane into isopropanol, mixing evenly, heating at 70° C. for reaction, and filtering after 6 hours to obtain grafted beads; S6: Wash the grafted beads with water, transform them with hydrochloric acid for 1 hour, filter, wash them with water, and dry them to obtain a large-capacity adsorption resin.
[0049] Example 10 This embodiment includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 150g liquid wax, 150g gasoline, 3g BPO, 3g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 70g sodium chloride, 7g methylene blue, 7g gelatin, 25g porous calcium carbonate, 200g 1-bromoheneicosane, and 2000ml isopropanol.
[0050] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride, sodium chloride, and porous calcium carbonate are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, and finally heated to 97° C., kept warm for 3.5 hours, and then cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: The intermediate product, monochloromethyl ether, sulfuric acid and catalyst were mixed evenly, heated to 48°C, kept warm for 10.5 hours, cooled to 25°C, washed with methanol twice, distilled, added with liquid alkali, adjusted to pH 8, stirred for 1 hour, filtered, and chloromethylated beads were obtained; S4: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the chloromethylated beads, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the quaternized beads were obtained by filtration and distillation; S5: adding quaternized beads and 1-bromoheneicosane into isopropanol, mixing evenly, heating at 70° C. for reaction, and filtering after 6 hours to obtain grafted beads; S6: Wash the grafted beads with water, transform them with hydrochloric acid for 1 hour, filter, wash them with water, and dry them to obtain a large-capacity adsorption resin.
[0051] Comparative Example 1: This comparative example includes the following components by mass: 220g styrene, 220g divinylbenzene, 30g methyl acrylate, 50g toluene, 80g isobutanol, 80g normal alkanes, 100g liquid wax, 150g gasoline, 3g BPO, 1g AIBN, 8g liquid bromine, 8g nitrobenzene; 2100g water, 8g cellulose, 8g calcium lignin sulfonate, 8g boric acid, 60g calcium chloride, 10g sodium chloride, 7g methylene blue, and 7g gelatin.
[0052] The preparation steps are as follows: S1: Styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine and nitrobenzene are mixed uniformly to obtain a monomer formulation; water, cellulose, calcium carbonate, boric acid, calcium chloride and sodium chloride are mixed to obtain an aqueous phase mixture; the monomer formulation and the aqueous phase mixture are mixed uniformly, first heated to 78° C., kept warm for 2 hours, then heated to 89° C., kept warm for 6.5 hours, finally heated to 97° C., kept warm for 3.5 hours, and cooled to 60° C. to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: Trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine were added dropwise to the intermediate product, the temperature was raised to 32° C., the reaction was kept warm for 11 hours, and the mixture was filtered and distilled to obtain quaternized beads; S4: The quaternized beads are washed with water, converted with hydrochloric acid for 1 hour, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
[0053] Performance test test 1: Specific surface area: The specific surface area of the adsorption resins prepared in the examples and comparative examples was tested by a fully automatic BET specific surface (area) analysis tester. The results are shown in Table 1.
[0054] Test 2: Static adsorption test: Static adsorption was used to determine the adsorption performance of the resins prepared in the examples and comparative examples for heavy metal ions. 0.1 g of the resin was placed in 50 mL of 200 mg·L -1 Heavy metal ion Cu 2 + solution in a conical flask, shake at 150 rpm, and record the adsorption amount of the resin after 8 hours. The results are shown in Table 1. The adsorption amount of the resin is calculated according to the following formula: Where qe is the equilibrium adsorption capacity, mg·g –1 ; C0 and Ce are the initial concentration and equilibrium concentration of metal ions in the solution, mg·L –1 ; m is the mass of the adsorption resin, g. The results are shown in Table 1.
[0055] Test three: Annual dissolution rate (360 cycles) test method: measure 10g of adsorption resin, dry to constant weight w1 (accurate to 0.1mg), adsorption and desorption is one cycle, after 30 cycles, take out the adsorbent, dry to constant weight w2 (accurate to 0.1mg), annual dissolution rate (360 cycles) La = (w1-w2) / w1 / 30x360x100%, the results are shown in Table 2.
[0056] Table 1 <![CDATA[Specific surface area / m 2 ×g -1 > <![CDATA[Adsorption capacity mg×g -1 > Example 1 955 90.1 Example 2 952 90.1 Example 3 957 90.7 Example 4 910 85.4 Example 5 903 86.2 Example 6 921 83.1 Comparative Example 1 457 79.1 In combination with Examples 1-6, Comparative Example 1 and Table 1, the present application adopts multiple monomers to co-polymerize to prepare the adsorption resin and then chloromethylates and quaternizes it, limits the process parameters of each step, and the obtained adsorption resin has a suitable degree of cross-linking and a large adsorption capacity.
[0057] Table 2 <![CDATA[Adsorption capacity mg×g -1 > Annual dissolution rate (360 cycles) Example 3 90.7 6.2% Example 7 96.9 3.4% Example 8 95.7 2.1 Example 9 95.5 1.4 Example 10 95.7 3.1% In combination with Example 3, Example 7 and Table 2, the present application adds porous calcium carbonate as a skeleton to the monomer, and the obtained adsorption resin has a larger adsorption capacity and a lower annual dissolution loss rate.
[0058] In combination with Example 3, Examples 8-10 and Table 2, the present application grafts 1-bromododecane and 1-bromooctadecane on the surface of the quaternized beads and limits the mass ratio, and the long and short chain alkanes form a certain entanglement. The prepared adsorption resin porous calcium carbonate is not easy to fall out, the resin is not easy to deform, the strength is higher, and the annual dissolution loss rate is lower.
[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a large-capacity adsorption resin for water treatment, characterized in that: The steps include: S1: Evenly mix styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene to obtain a monomer formulation; evenly mix water, cellulose, calcium carbonate, boric acid, calcium chloride, and sodium chloride to obtain an aqueous phase mixture; evenly mix the monomer formulation and the aqueous phase mixture, raise the temperature, and keep the temperature to react to obtain a polymer; S2: washing the polymer with water, washing with an organic solvent, drying the powder and sieving it to obtain an intermediate product; S3: uniformly mix the intermediate product, monochloromethyl ether, sulfuric acid and catalyst, raise the temperature, keep the temperature for reaction, lower the temperature, wash with organic solvent, distill, add liquid alkali, adjust the pH, stir, filter, and obtain chloromethylated beads; S4: adding trimethylamine solution, dimethylamine solution, tri-n-butylamine, polyethylene polyamine, pyridylamine, methylal, and urotropine dropwise to the chloromethylated beads, raising the temperature, keeping the temperature to react, filtering, and distilling to obtain quaternized beads; S5: The quaternized beads are washed with water, converted with hydrochloric acid, filtered, washed with water, and dried to obtain a large-capacity adsorption resin.
2. The method for preparing a large-capacity adsorption resin for water treatment according to claim 1, characterized in that: Said The mass parts of the components in the monomer formulation in S1 are as follows: 200-250 parts of styrene, 180-250 parts of divinylbenzene, 15-40 parts of methyl acrylate, 40-60 parts of toluene, 50-100 parts of isobutanol, 50-100 parts of normal alkanes, 100-200 parts of liquid wax, 100-200 parts of gasoline, 2-5 parts of BPO, 3-5 parts of AIBN, 5-10 parts of liquid bromine, and 5-10 parts of nitrobenzene; the mass parts of the components in the aqueous phase mixture are as follows: 2000-2200 parts of water, 5-10 parts of cellulose, 5-10 parts of calcium lignin sulfonate, 5-10 parts of boric acid, 50-70 parts of calcium chloride, 50-80 parts of sodium chloride, 2-10 parts of methylene blue, and 5-10 parts of gelatin; Among the components in S3, the catalyst is zinc chloride, and the mass volume ratio of the intermediate product, monochloromethyl ether, sulfuric acid, and zinc chloride is: 4:10:1:1; The mass volume ratio of chloromethylated beads, trimethylamine, dimethylamine, tri-n-butylamine, polyethylene polyamine, pyridinamine, methylal, and urotropine in S4 is 2:(1.8-2.1):(1.8-1.9):(1-1.1):(2-2.2):1:(3-3.5):
2.
3. The method for preparing a large-capacity adsorption resin for water treatment according to claim 1, characterized in that: The heating and heat preservation reaction in S1 comprises the following steps: firstly heating to 78-82°C, keeping warm for 2-3 hours, then heating to 85-89°C, keeping warm for 5.5-6.5 hours, finally heating to 93-97°C, keeping warm for 2.5-3.5 hours, and cooling to below 70°C.
4. The method for preparing a large-capacity adsorption resin for water treatment according to claim 1, characterized in that: The water washing and organic solvent washing in S2 include the following steps: washing with 50-80°C water until the water is clear, then introducing 60-80°C toluene to elute until the liquid wax and styrene residues are less than 100 ppm, then introducing 50-60°C methanol to elute until the toluene residue is less than 100 ppm, and finally washing with water until no solvent remains.
5. The method for preparing a large-capacity adsorption resin for water treatment according to claim 1, characterized in that: In S3, the heating temperature is 48-50° C., the heat preservation reaction time is 9.5-10.5 hours, the cooling temperature is less than 30° C., the organic solvent washing includes methanol or methylal washing 2-4 times, the pH value is 8-10, and the stirring time is more than 0.5 hour.
6. The method for preparing a large-capacity adsorption resin for water treatment according to claim 1, characterized in that: The temperature of S4 is raised to 28-32° C., and the heat preservation reaction time is 9-11 hours.
7. The method for preparing a large-capacity adsorption resin for water treatment according to claim 2, characterized in that: The monomer formulation in S1 further includes 20-30 parts by mass of porous calcium carbonate.
8. The method for preparing a large-capacity adsorption resin for water treatment according to claim 7, characterized in that: The method further comprises the following steps: adding the quaternized beads and the long-chain halogenated alkane prepared in S4 into isopropanol, stirring evenly, and heating for reaction.
9. The method for preparing a large-capacity adsorption resin for water treatment according to claim 8, characterized in that: The long-chain halogenated alkane comprises 1-bromododecane and 1-bromooctadecane in a mass ratio of 1:(1.2-1.4).
10. A large-capacity adsorption resin for water treatment, characterized in that: The method for preparing a large-capacity adsorption resin for water treatment according to any one of claims 1 to 9 is obtained.